Improving housing conditions: Labelled loans in Kenya and Uganda - Amreen Choda; Annekathrin Schoofs; Noel Verrinder (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
We evaluate a non-governmental housing microfinance intervention that attempts to improve housing conditions for low income populations by simultaneously offering them a labelled loan and non-financial technical support. Using household survey data from Kenya and Uganda, we first show evidence for the successful targeting of our labelled loans because 95% of clients used the loan for the intended housing improvement. Second, our results suggest that access to small, short-term loans enables households to invest in housing upgrades that can significantly improve both the characteristics of their dwelling and their satisfaction with their dwelling. These effects are robust to four different estimation approaches (difference-in-differences, inverse probability weighting, matching, and ordinary least squares with postdouble selection Lasso). – – Wir evaluieren eine Mikrofinanzintervention, die darauf abzielt, die Wohnverhältnisse für einkommensschwache Bevölkerungsgruppen in Kenia und Uganda zu verbessern, indem sie gleichzeitig einen gelabelten Kredit und nicht-finanzielle technische Unterstützung erhalten. Anhand von Haushaltsbefragungen zeigen wir zunächst, dass 95 % der Bankkunden den Kredit für die gelabelte Finanzierung nutzen und dementsprechend in ihre Wohnsituation investieren. Zweitens deuten unsere Ergebnisse darauf hin, dass der Zugang zu kleinen, kurzfristigen Krediten es den Haushalten ermöglicht die Eigenschaften ihrer Wohnung als auch ihre Zufriedenheit mit der Wohnung zu verbessern. Diese Effekte sind gegenüber vier verschiedenen Schätzungsverfahren robust (Differenz-von-Differenzen-Ansatz, inverse Wahrscheinlichkeitsgewichtung, Matching und Lasso).
Keywords: I15; I31; O18; 330; Housing conditions; microfinance; health; Uganda; Kenya